(untitled) (Bangladesh Medical Journal, 2009)
A study on 6492 new cancer patients was done at National Institute of Cancer Research & Hospital (NICRH), Mohakhali, Dhaka from January 2006 to December 2006. Histopathologically confirmed cancer patients; patients having radiological or clinical evidence of malignancy were included in the study. Majority of the patients were from Dhaka division (47.8%) and next from Chittagong division (22.5%). There were 3824 male and 2668 female patients in the study. The male female ratio was 1.4:1.The majority of cancer occurred in middle and old age. In adult male Lung cancer ranked the top (909, 24.1%) followed by cancer of lymph node and lymphatic (264, 7.0%), Laryngeal carcinoma (247, 6.5%) and Oesophageal Carcinoma (199, 5.3%). Breast cancer (24.48) was the major malignancy amongst adult female (633, 23.3%) followed by that of the cervix (583, 21.4%), Lung (153, 5.6%) and Oral cavity (116, 4.3%). In pediatric patients malignancy of lymphatics and lymphoid tissue led the tally while in geriatric group Lung cancer found to be more prevalent. DOI: 10.3329/bmj.v37i1.3599 Bangladesh Medical Journal 37(1) 2008 2-5